Tecnologias da Informação e Comunicação e o salto em distância: possibilidades de utilização de um DVD didático para o ensino do atletismo escolar - Silva, Tiago Pedicini Ferreira da [UNESP] (2014)
As one of the contents of physical education, the teaching of athletics in Brazilian schools has been deprecated instead of other sports. Therefore, this research aimed to produce an educational DVD on the long jump aiming his teaching in elementary school, evaluating, with a group of teachers through a focus group, the possibility of using it in School Physical Education. Of qualitative nature , this research was carried out in three steps: 1) literature review, selecting the contents to be on this educational DVD and determining the target audience; 2) Filming, recording videos, taking images, editing and production of didactic DVD and 3) the educational DVD evaluation through via focus group. The results showed that teachers, although not teach the long jump in their classes, because of the little knowledge about, the lack of structure and lack of student interest, consider it as an important content and which has to be taught in physical education classes. In this sense and in assessing the educational DVD “Long Jump showed up excited to teach it, recognizing the feasibility of using this material in physical education classes. At the end of this research it was concluded that such teaching resources are welcome, in particular, can be used for adapting to the needs of each teacher/school